Androgens Regulate T47D Cells Motility and Invasion through Actin Cytoskeleton Remodeling - Montt-Guevara, Maria Magdalena; Shortrede, Jorge Eduardo; Giretti, Maria Silvia; Giannini, Andrea; Mannella, Paolo; Russo, Eleonora; Genazzani, Alessandro David; Simoncini, Tommaso (Frontiers in Endocrinology, 2016)
The relationship between androgens and breast cancer is controversial. Androgens have complex effects on breast cancer progression and metastasis. Moreover, androgens receptor (AR) is expressed in approximately 70% to 90% of invasive breast carcinomas, which has prognostic relevance in basal-like cancers and in triple negative breast cancers. Recent studies have associated the actin-binding proteins of the Ezrin-Radixin-Moesin (ERM) family with metastasis in endocrine-sensitive cancers. We studied on T47D breast cancer cells whether androgens with different characteristics, such as testosterone (T), dihydrotestosterone (DHT) and dehydroepiandrosterone (DHEA) may regulate breast cancer cell motility and invasion through the control of actin remodelling. We demonstrate that androgens promote migration and invasion in T47D via Moesin activation. We show that T and DHEA exert their actions via the AR and estrogen receptor (ER), while the non aromatizable androgen – DHT only recruits AR. We further report that androgen induced significant changes in actin organization with pseudopodia along with membrane ruffles formation, and this process is mediated by Moesin. Our work identifies novel mechanisms of action of androgens on breast cancer cells. Through the modulation of Moesin, androgens alter the architecture of cytoskeleton in T47D breast cancer cell and promote cell migration and invasion. These results could help to understand the biological actions of androgens on breast cancer, and eventually to develop new strategies for treatment of breast cancer.